A solution to Darwin's dilemma of 1859: exceptional preservation in Salter's material from the late Ediacaran Longmyndian Supergroup, England - Callow, R; Brasier, M (2009)
Study of historical and fresh collections from the Longmyndian Supergroup sheds new light on Ediacaran microbial communities and taphonomy. First reported by Salter in 1856, and noted by Darwin in the Origin of Species in 1859, a range of macroscopic bedding plane markings are already well known from the Longmyndian supergroup. Here we report filamentous and sphaeromorph microfossils, variously preserved as carbonaceous films, by aluminosilicate permineralization and as bedding plane impressions. This supports a long-suspected link between wrinkle markings and microbes, and draws further attention to our hypothesis for a taphonomic bias towards high-quality soft tissue preservation in the Ediacaran Period. © 2009 Geological Society of London.